Análise da aplicação de casca de café nas propriedades de tijolos de solo-cimento - Castro, Eliziane Denize de (2017)
The concern with sustainability is an aspect that currently reaches all production sectors, including that of civil construction, which demands materials that cause less environmental impacts in its fabrication. In this context, the soil-cement brick, made from a homogeneous mixture of soil, cement and water, is an alternative given that it does not demand burning in firewood oven, avoiding deforestation and air pollution. There is also the possibility of using agricultural waste in its fabrication, thus contributing to decrease the inadequate disposal of these materials. This work aimed at studying the effects of incorporating particles of coffee peel (Coffea arabica L.), in different ages, in partial substitution of cement over the physical, mechanical and thermal properties of the soil-cement. For the production of the bricks, we used type CP II F-32 Portland cement, particles of coffee peel and soil, which, due to its initial characteristics, demanded particle correction with sand. With the definition of initial percentage of cement in the mixture at 10%, the percentages of coffee peel in relation to cement were of 5%, 10%, 15% and 20%. The bricks submitted to absorption, simple compression (at ages of 4, 28 and 56 days), thermal isolation (at 28 days) and durability (at 56 days) trials. The results showed that the partial substitution of cement for coffee peel presented significant effect over the properties, which, with the increase in coffee peel content, the values obtained for water absorption, variation of volume and loss of mass in the durability trial increased, while resistance to compression and apparent specific dry mass decreased. The interaction between the content of peel and the age of the samples was significant only for the variable resistance to compression. The thermal conductivity was not influenced by the increase in plant residue. However, the value found was inferior to that determined by the NBR 15220-2 (ABNT, 2005), which demonstrates the isolating potential of the brick. Only the treatment with 0% of coffee peel at 56 days of age reached the minimum resistance of 2MPa, as occurred with water absorption at 20%, requisites of NBR 8491 (ABNT, 2012). In general, we conclude that the substitution of cement for coffee peel, in the manner done in this work, presented no significant results regarding the normative requisites. However, the possibility of employing this waste in soil-cement mixtures cannot be disposed of, given that other variables interfered in the quality of the material. Further studies must be developed seeking to optimize the production process and to improve the compatibility between the plant material and the cement.